RELEVANCE OF GRAMMAR - Singh, Manoj Kumar (International Journal of Research -GRANTHAALAYAH, 2022)
This piece of paper presents the practical and theoretical utility of grammar. From the very beginning, grammarians implemented their basic concept to the readers what we find today. Grammar, as is known, is a science that articulates us to intuit both writing and speaking English in a correct and concise way. Orthography, etymology, syntax, punctuation, and prosody are said to be the bases of grammar. Without utterances of these words, nothing can be imagined in grammar. They have been arranged in a sequence so that every next part may be semantic in use. Orthography is the smallest unit of etymology. The world of syntax is vast. Punctuation balances the sentences whereas prosody personifies them.